Cross-layer mimo-links exploiting packet switching and adaptive modulation for TCP/IP enabled volcano monitoring networks - Erwin Anggadjaja (2014)
The effects of sub-channel packet routing and adaptive modulation (AM) are explored in this thesis for MIMO linking system under differing channel conditions. The challenges is to exploit time-varying imbalances between logical sub-channels by different cross-layer routing and modulation strategies to improve overall goodput. An investigation of several network simulation tools is presented in order to choose an appropriate simulation and modelling tool, particularly to be used and fitted to the wider EOS (Earth Observatory of Singapore) project. Several important aspects such the availability of protocol model, simulation capabilities and academic acceptance, emphasis on unsophisticated attributes such as debugging and GUI environment, open source nature, and cost issues are also considered to accommodate non-specialist users (i.e. earth scientists) who are the target recipients of the wider EOS research project. Discussions and analysis are given prior to selecting OMNeT++ as the basis for the ongoing simulations. Further assessments were made and verified by presenting a simulated model implementing segmentation and reassembly (SAR) concepts combined with local error control mechanism in the form of ACK/NACK triggered retries with timeout. As a main contribution, MIMO sub-channel characteristics are modelled in terms of frame-by-frame BER, channel delay, and data rate to explore the effect of channel BER imbalance by implementing frame-by-frame sub-channel re-routing and retry mechanism with the aim of improving overall goodput. Several simulations are derived which make use of the TCP protocol through the use of an open-source simulation package within the OMNeT++ environment named INET. Scenario models are created from a single protocol link and then extended into dual wireless sub-channels, and the final interesting quad-parallel independent link model (Quad-PILM). For both dual- and quad- link models, two novel switching methods: SWS and PLD, and two retry scenarios are set up: RDL and RRL, to explore how re-transmissions can be adjusted to take advantage of short-term channel imbalances. We investigate the system in the light of goodput under various channel differences. As a final model, a BER-directed adaptive modulation switching scheme, based on a quad- parallel link model, is evaluated. This cross-layer design relates to physical, data link, and transport layers. Although it technically breaks a strict layering concept, even a simple switching scheme with a very clean layered interface, is shown to yield a performance improvement. Based on our analysis, we determine the degree of improvement achievable through the proposed scheme, and show that the technique may be advantageous for multiple antenna systems employed in cross-layer designs. This thesis demonstrates that even quite simple switching heuristics and two-way packet re-routing mechanisms can provide an overall improvement in a common real-world situation where MIMO sub-channels exhibit slightly unequal error rates for durations of one or more transmission frames.